Introduction to small area estimation techniques a practical guide for national statistics offices. - Asian Development Bank. (Metro Manila, Philippines Asian Development Bank, 2020)
This guide to small area estimation aims to help users compile more reliable granular or disaggregated data in cost-effective ways.It explains small area estimation techniques with examples of how the easily accessible R analytical platform can be used to implement them, particularly to estimate indicators on poverty, employment, and health outcomes. The guide is intended for staff of national statistics offices and for other development practitioners. It aims to help them to develop and implement targeted socioeconomic policies to ensure that the vulnerable segments of societies are not left behind, and to monitor progress toward the Sustainable Development Goals.
Keywords: Poverty -- Statistics; Poverty -- Statistical methods; Electronic books